Hak Menolak Wajib Militer: Catatan atas RUU Komponen Cadangan Pertahanan Negara - Robby Simamora (Jurnal Konstitusi, 2014)
The military service agenda proposed Components of the National Defense Bill sows controversy. The absence of protection of citizens who exercised their right of conscientious objection to military service could potentially lead to violations of human rights if the military service must be implemented as it happens in other countries. Guarantee the protection of conscientious objection as part of the civil and political rights is a necessity if the government want to impose military service, considering Indonesia had acknowledged the existence of conscientious objector in the history of its military service policy.